EU3+-O2- associates luminescence in Ba2SiO4 - Pires, Ana Maria [UNESP]; Davolos, Marian Rosaly [UNESP]; Malta, O. L. (Elsevier B.V., 1997)
Results on the luminescence properties of Eu3+ in Ba2SiO4 sites and the presence of Eu3+-O2- associates are reported. The Ba2SiO4:Eu3+ emission spectra showed two groups of transitions that might be assigned to the D-5(0) --> F-7(0) one. In each group at least two lines were observed. This is possibly related to the different emission centers, attributed to Eu3+ occupying the Ba2+ sites, and to Eu3+-O2- associates in interstices. Excitation spectra presented two CT bands at 270 and 340 nm related to each emission center.
Keywords: Eu3+-O2- associates; anomalous Eu3+ 5D0->F-7(0) transition; barium orthosilicate